Determinants of SMEs Intention towards Adoption of Banking Products: A Comparative Study of Islamic and Conventional Banks in Pakistan - Rabia Rasheed; Hafiz Abdur Rashid (Journal of Business and Social Review in Emerging Economies, 2021)
SMEs play the role of backbone of the economic and business activities. Growth and development of SMEs is also dependent to a major extent on the availability of suitable banking products in line with their specific needs and wants. Therefore, this study has emphasized that understanding SMEs’ financial behavior towards Islamic/conventional banking products is prerequisite for policy makers and managers of banking and non-banking financial institutions. A conceptual framework has been discussed in present study to understand financial behavior of SMEs. Moreover, to identify the determinants of SMEs owner-managers behavioral intention which influence their financial decisions towards adoption of Islamic/conventional banking products in Pakistan. Further suggested that researchers can examine the influence of these factors on financial behavior of SMEs as well as to find out owner/managers preferences to choose banking Islamic/conventional products.